HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN MINUM OBAT ANTI TUBERKULOSIS (OAT) DI UPT PUSKESMAS TELADAN - FIRDAUS ROSA; ISTI ILMIATI FUJIATI (JURNAL ILMIAH MAKSITEK, 2020)
High number of tuberculosis (TB) cases and low number of medication achievement which one of cause is drop out makesthe treatment longer. Besides, the number of Multi Drug Resistance (MDR) and complication of TB will high. This quantitativecross sectional study was taken from 69 respondentby total sampling at UPT Puskesmas Teladan, Medan City. The datawas collected through two questionnaires, they are Morinsky Medication Adherence Scale (MMAS) and family supportquestionnaire. Analyze was used univariate and Chi Square test for bivariate. Persentage of respondents with good familysupport are 60.9%, respondents with bad family support are 39.1%. Persentage of respondents with good medicationadherence are 73.9%, and bad medication adherence are 26.1%. The data result obtained p value = 0.00 which islessthan0.05. There is significant relationship between the variables of family support to variable medication adherence.However, involving the family within the treatment is best recommend on medication treatment.